De phrases illustrant la grammaire au texte porteur de sens : quelques réflexions sur des manuels de latin - Antje-Marianne Kolde (Recherches en didactique des langues et des cultures)
The contribution examines the question whether the Latin manuals develop in a similar way to those of modern languages: do they replace also the aim of grammatical and lexical acquisition by the communication objectives? Both Latin manuals and these of modern languages offer activities on and around texts; for comparison with the modern language textbooks, the contribution offers reflections on the place which Latin textbooks of the late twentieth century and early twenty-first century in western Switzerland grant to texts and the activities proposed in connection with the texts.